Enhancing Mental Health Support for Unaccompanied Asylum- Seeking Young People (UASYP): A Collaborative Pathway in Aberdeen - Praveen Kumar; Claire Hardie (BJPsych Open)
Aims: This initiative aimed to establish a structured and collaborative pathway to address the mental health and psychosocial needs of Unaccompanied Asylum-Seeking Young People (UASYP) in Aberdeen. The project sought to provide trauma-informed, culturally sensitive interventions while fostering partnerships with local and national agencies to ensure comprehensive support. In 2023, the UK received 3,412 applications from Unaccompanied Asylum-Seeking Children (UASC), with Scotland accommodating a proportionate share through the National Transfer Scheme.